Irrationality in Donald Davidson - Álvarez Layna, José Ramón (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This article addresses irrationality within the thought of the American philosopher Donald Davidson. Consequently, it represents a study around the evolution of the collection of academic papers by Davidson himself. The collection of papers by Donald Davidson, lets us articulate the evolution of his concerns around the problem of rationality-irrationality. Therefore, the problem of rationality-irrationality came to find a place within the wider frame of the general development of the philosophical task carried out by Donald Davidson around metaphysics, languages, truth and history.